Ising model with competing interactions on Cayley tree of order 4: an analytic solution - Ali, Rukiah; Pah, Chin Hee (2011)
For the Ising model with competing interactions on the fourth-order Cayley tree, we find the critical curve separate the region of phase transition and no phase transition. We investigate a phase transition phenomena from the associated dynamical system point of view. An alternative approach but basic technique is given to study the stable fixed points of these dynamical systems.